2015
DOI: 10.18632/oncotarget.4622
|View full text |Cite
|
Sign up to set email alerts
|

MiR-215, an activator of the CTNNBIP1/β-catenin pathway, is a marker of poor prognosis in human glioma

Abstract: MicroRNA-215 (miR-215) promotes tumor growth in various human malignancies. However, its role has not yet been determined in human glioma. Here, we found that levels of miR-215 were higher in glioma tissues than in corresponding non-neoplastic brain tissue. High miR-215 expression was correlated with higher World Health Organization (WHO) grades and shorter overall survival. Multivariate and univariate analysis indicated that miR-215 expression was an independent prognostic factor. We also found that TGF-beta1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Two recent studies reveal that miR-215-5p up-regulation in gliomas is associated with poor prognosis [31, 32]. Consistently, we also find that miR-215-5p is up-regulated in gliomas and miR-215-5p level is higher in high-grade gliomas.…”
Section: Discussionsupporting
confidence: 90%
“…Two recent studies reveal that miR-215-5p up-regulation in gliomas is associated with poor prognosis [31, 32]. Consistently, we also find that miR-215-5p is up-regulated in gliomas and miR-215-5p level is higher in high-grade gliomas.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, we conducted in situ hybridization (ISH) analyses to examine levels of miR-215 on GBM tissue microarrays and found that higher level of miR-215 expression was correlated with poor survival (Figure 1D). The clinical importance of miR-215 in gliomagenesis is also supported by a recent report that miR-215 expression is positively correlated with poor prognosis in glioma patients (Tong et al, 2015). In sum, these data strongly indicate that miR-215 is a hypoxia-induced miRNA in GICs, and it acts to promote GBM progression probably by mediating the hypoxic responses of GICs.…”
Section: Resultsmentioning
confidence: 66%
“…Therefore, we searched miR-215 target genes by miRTarBase or those that may be linked to immunological surveillance or residual CML stem cells; miR-215 has previously been demonstrated to be dysregulated in several human malignancies and to be correlated with tumor progression [ 19 , 21 , 26 , 27 ]. Meta-analyses have revealed that elevated miR-215 expression is correlated with poor prognosis in renal cell carcinomas [ 28 ], glioma [ 29 ] and pancreatic cancer [ 30 ]. In contrast, decreased expression was associated with advanced disease stage in colorectal cancer [ 31 ], and miR-192-5p/215 is a putative tumor suppressor in non-small cell lung cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%